2022
DOI: 10.1002/pros.24406
|View full text |Cite
|
Sign up to set email alerts
|

Does castration status affect docetaxel‐related adverse events? :Identification of risk factors for docetaxel‐related adverse events in metastatic prostate cancer

Abstract: Background Docetaxel‐related adverse events (AEs) such as neutropenia and febrile neutropenia (FN) can be life‐threatening. A previous in vivo study raised the hypothesis that the castration status affects the rate of hematologic AEs. We aimed to investigate the impact of castration status on the incidence of docetaxel‐related AE in metastatic prostate cancer (mPCa) patients. Methods We retrospectively analyzed the records of 265 mPCa patients treated with docetaxel, comprising 92 patients with metastatic horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…At present, there are few clinical cases of targeted therapy for mCRPC. Some patients with mCRPC cell migration and invasion, so as to inhibit tumor growth and metastasis [11] . In addition, docetaxel may also rely on the regulation of tumor stem cells to inhibit tumor recurrence and drug resistance [12] .…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are few clinical cases of targeted therapy for mCRPC. Some patients with mCRPC cell migration and invasion, so as to inhibit tumor growth and metastasis [11] . In addition, docetaxel may also rely on the regulation of tumor stem cells to inhibit tumor recurrence and drug resistance [12] .…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis showed that ARSI-based doublet therapy had high probabilities for a net clinical benefit; however, docetaxel-based doublet as well as triplet therapy appeared unlikely to be beneficial [ 32 ]. Docetaxel is known to increase the risk of severe adverse events and can reduce the patient quality of life [ 2 , 33 ]. Our previous meta-analysis confirmed that docetaxel-based combination had a higher likelihood of severe adverse events, with triplet therapies being the highest adverse event rates [ 2 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel is known to increase the risk of severe adverse events and can reduce the patient quality of life [ 2 , 33 ]. Our previous meta-analysis confirmed that docetaxel-based combination had a higher likelihood of severe adverse events, with triplet therapies being the highest adverse event rates [ 2 , 33 ]. In the subgroup analysis of the ARASENS trial, 74% of patients with low-volume disease who received triplet therapy experienced severe adverse events [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 Of note, intensified therapy with DOC and/or ARSIs causes drug-specific AEs where DOC-related hematological AEs are sometimes life-threatening. 52 The goal of mHSPC management is to provide optimal outcomes by balancing the harm-to-benefit ratio. However, in this study, we did not assess the likelihood of AEs due to the lack of data stratified by visceral metastasis.…”
Section: Discussionmentioning
confidence: 99%